First record of Acanthocephala parasites eggs in coprolites preliminary assigned to Crocodyliformes from the Adamantina Formation (Bauru Group, Upper Cretaceous), São Paulo, Brazil - DANIEL F.F. CARDIA; REINALDO J. BERTINI; LUCILENE G. CAMOSSI; LUIZ A. LETIZIO (Anais da Academia Brasileira de Ciências, 2019)
Abstract Abstract: This study presents the oldest record of Acanthocephala parasite eggs in coprolites preliminary assigned to Crocodyliformes, recovered in the region of Santo Anastácio Municipality, Southwestern São Paulo State. For this, a paleoparasitological investigation was carried out on 53 mineralized coprolites (complete or fragmented), with round shape or cylindrical shape of rounded or pointed ends, 0.2 - 3.9 cm in length x 0.1 - 2.4 cm in diameter, 3.7 grams in weight, and absence of food remains. Individual samples of the surface and internal portions of each coprolite were extracted by electric drill, dissociated with Cloridic Acid 10% solution, washed with Distilled Water, and filtered in granulometric screen Mesh / Tyler 325. After laboratory processing, the sediments retained on the granulometric screen was studied with Glycerin under optical microscopy, and the presence of four Acanthocephala eggs could be observed in sample of only one of these ichnofossils. All specimens were well preserved and showed 72.5 - 85 µm in length x 27.5 - 50 µm in width, elliptical shape, three concentric and thick shells, and embryos in their interior. This study inaugurates investigations and knowledge about Paleoparasitology in Crocodyliformes coprolites from the Bauru Group, Upper Cretaceous from the Paraná Basin.